Effects of dapagliflozin on blood volume status and vascular outcomes in clinically stabilized heart failure patients after an acute decompensated heart failure event (DAPA-VOLVO study): Protocol of a double-blind randomized controlled clinical trial. - Konstantinos Bitos; Natallia Laptseva; Thomas Haider; Valentina A Rossi; Matthias P Nägele; Jens Barthelmes; Frank Ruschitzka; Isabella Sudano; Andreas J Flammer (PLoS ONE)
Introduction Heart failure (HF) is among the most prevalent health issues worldwide and is associated with high mortality. Adequate decongestion remain the main clinical challenge in HF management. Sodium glucose cotransporter-2 inhibitors (SGLT-2i) have been recently introduced as a new treatment option in patients with HF irrespective of left ventricular ejection fraction. Although the favorable effects of SGLT-2i are profoundly evident, the underlying mechanisms are not yet well understood. The aim of this study is to provide novel insights into the effects of dapagliflozin, a SGLT-2i with proven cardiovascular benefit, on blood volume profile and vascular function in HF patients who had a recent event of acute decompensated heart failure (ADHF). Methods Eighty adult patients with diagnosis of de novo or chronic HF (NYHA class II-IV), clinically stabilized after an ADHF event and with preserved renal function, who were not on treatment with SGLT-2i, are aimed to be included. The patients are randomized with 1:1 allocation to either dapagliflozin 10 mg p.o. once daily or placebo in addition to guideline-directed medical therapy. The primary outcome is the mean change in plasma volume status (PVS) in the dapagliflozin group compared to placebo. PVS is assessed via optimized carbon monoxide rebreathing technique, a reliable and safe method to measure total hemoglobin mass and to estimate blood volume profile, i.e., blood volume, plasma volume and red blood cell volume. Secondary outcomes include differences between the two study groups regarding blood volume profile, micro- and macro-vascular function assessed by retinal vessel analysis and flow-mediated vasodilation, respectively, changes in body water distribution, quality of life, exercise capacity, echocardiographic and laboratory parameters. Ethics and dissemination The study has been approved by the Cantonal Ethics Committee Zurich (BASEC-Nr.:2020-01920, Swissmedic-Nr.:2020DR4175) and has been registered at www.ClinicalTrials.gov‌ (NCT04869124). The results will be published in a peer-reviewed medical journal.